Assessment of the Capacity to Implement Competence-based Curriculum in Isiolo County Primary Schools, Kenya - Atikiya, Dr. Rukia (International Journal of Scientific Research and Management (IJSRM), 2021)
To address the shortfall of the outcome system of education (8-4-4) that is currently underway and to improve quality of education by making it more relevant to the need of the society, the Kenyan government embarked on yet another educational reform. This was the implementation of the competence-based curriculum which was rolled out in January, 2019 in pre- primary and lower primary levels of basic education. The purpose of this study was to assess the capacity to implement competence-based-curriculum by Isiolo County Primary Schools. Descriptive research design was employed. The study sample comprised of 48 head teachers, 48 pre-school teachers, 13 parents with children in lower primary who were picked using snowballing, and 2 Ministry of education and County education officials who were picked using convenient sampling. Questionnaire and interview were the main tool used for data collection. The data was analyzed using descriptive statistics and thematic analysis for qualitative data. The findings of the study revealed that the teaching and learning materials are not adequate, the learning environment is not appropriate, inadequate teachers for competence-based curriculum delivery. Whilst most of the schools are connected to electricity, the schools had no computer labs, computers or libraries, which are key resource in the delivery of the competence-based curriculum. The study further revealed that the pre-school teachers are still ill-equipped to implement the new curriculum despite being trained and lacked computer skills. Majority of parents are also not sensitized on the content and their role in competence-based curriculum implementation hence not able to contribute positively. The study recommends provision of adequate learning and teaching materials, improvement of learning infrastructure, recruitment of additional teachers, enhancement of capacity of pre-school teachers through further training on CBC as well as computer skills, sensitization of parents as well as provision of additional finances to schools to ensure successful implementation of competence-based-curriculum.